The Risks of miRNA Therapeutics: In a Drug Target Perspective - Zhang S; Cheng Z; Wang Y; Han T (Dove Medical Press, 2021)
Song Zhang, 1, 2 Zhujun Cheng, 3 Yanan Wang, 1 Tianyu Han 1 1Jiangxi Institute of Respiratory Disease, The First Affiliated Hospital of Nanchang University, Nanchang, 330006, People’s Republic of China; 2College of Pharmaceutical Sciences, Zhejiang University, Hangzhou, 310058, People’s Republic of China; 3Department of Burn, The First Affiliated Hospital of Nanchang University, Nanchang, 330006, People’s Republic of ChinaCorrespondence: Tianyu Han Email hantianyu87@163.comAbstract: RNAi therapeutics have been growing. Patisiran and givosiran, two siRNA-based drugs, were approved by the Food and Drug Administration in 2018 and 2019, respectively. However, there is rare news on the advance of miRNA drugs (another therapeutic similar to siRNA drug). Here we report the existing obstacles of miRNA therapeutics by analyses for resources available in a drug target perspective, despite being appreciated when it began. Only 10 obtainable miRNA drugs have been in clinical trials with none undergoing phase III, while over 60 siRNA drugs are in complete clinical trial progression including two approvals. We mechanically compared the two types of drug and found that their major distinction lay in the huge discrepancy of the target number of two RNA molecules, which was caused by different complementary ratios. One miRNA generally targets tens and even hundreds of genes. We named it “too many targets for miRNA effect” (TMTME). Further, two adverse events from the discontinuation of two miRNA therapeutics were exactly answered by TMTME. In summary, TMTME is inevitable because of the special complementary approach between miRNA and its target. It means that miRNA therapeutics would trigger a series of unknown and unpreventable consequences, which makes it a considerable alternative for application.Keywords: RNAi, miRNA, siRNA, therapeutics